The Predictive Value of N-Terminal Probrain Natriuretic Peptide for Infection in Patients With Acute Myocardial Infarction - Dai, YiNing; Wan, XiaoLiang; Liu, Can; Duan, ChongYang; Shao, Shuai; Chen, HongHuan; Wang, Litao; Lin, JiJin; Xue, Ling; Chen, JiYan; He, PengCheng; Liu, YuanHui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Infections increase the risk of poor outcomes in patients with ST-elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). However, predicting patients at a high risk of developing infection remains unclear. Moreover, the value of N-terminal probrain natriuretic peptide (NT-proBNP) for predicting infection is still unknown. Thus, we aimed to assess the relationship between NT-proBNP and the following development of infection, and clinical adverse outcomes in patients with STEMI undergoing PCI. Methods: STEMI patients undergoing PCI were consecutively enrolled from January 2010 to July 2016 and divided into groups according to baseline NT-proBNP levels: tertiles T1 (<988 pg/mL), T2 (988–3520 pg/mL), and T3 (≥3520 pg/mL). The primary endpoint was infection during hospitalization. Results: A total of 182 (27%) patients developed in-hospital infection. The incidence of infection increased from T1 to T3 (10.5, 17.7, and 54.5%, P < 0.001). NT-proBNP was an independent risk factor (adjusted odds ratio = 1.39, 95% confidence interval (CI) = 1.12–1.73, P = 0.003) and presented accurately predicting infection (area under curve = 0.774). Multivariate cox analysis showed that NT-proBNP was a significant risk factor for major adverse clinical events (MACE) at follow-up (adjusted HR = 1.92, 95% CI = 1.61–2.29, P < 0.001). Conclusion: The baseline NT-proBNP level has a good predictive value for infection and MACE in STEMI patients undergoing PCI.